基于杆长约束的变拓扑机构奇异性分析方法 - 郭兴辉; 秦伟; 侯少毅 (Jixie chuandong)
The classification about singularity of closed-chain variable topology mechanism is proposed and the technique for analysis of speed matrix of variable topology mechanism based on the length constraints is presented. The technique makes the construction of the speed matrixes for transformation of different configuration in variable topology mechanism more convenient.